Sealpox Virus in Marine Mammal Rehabilitation Facilities, North America, 2007–2009 - Amira Roess; Rebecca Levine; Laura Barth; Benjamin Monroe; Darin Carroll; Inger Damon; Mary Reynolds (Emerging Infectious Diseases, 2011)
Sealpox, a zoonotic disease affecting pinnipeds (seals and sea lions), can occur among captive and convalescing animals. We surveyed 1 worker each from 11 marine mammal centers and interviewed 31 other marine mammal workers to ascertain their knowledge of and experience with sealpox virus and to identify factors associated with sealpox virus outbreaks among pinnipeds in marine rehabilitation facilities. Demographic and health data were obtained for 1,423 pinnipeds at the 11 facilities. Among the 23 animals in which sealpox was clinically diagnosed, 4 arrived at the facility ill, 11 became ill <5 weeks after arrival, and 2 became ill >5 weeks after arrival; the timing of illness onset was unknown for 6 animals. Most infections occurred in pinnipeds <1 year of age. Nine affected animals were malnourished; 4 had additional illnesses. Sealpox had also occurred among workers at 2 facilities. Sealpox is a noteworthy zoonosis of rehabilitating convalescing pinnipeds; workplace education can help to minimize risks for human infection.